2020
DOI: 10.7150/thno.47037
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of estrogen-related receptor alpha-dependent hepatic VLDL secretion contributes to sex disparity in NAFLD/NASH development

Abstract: Rationale: Men and postmenopausal women are more prone to developing non-alcoholic fatty liver disease/steatohepatitis (NAFLD/NASH) than premenopausal women. However, the pathological links and underlying mechanisms of this disparity are still elusive. The sex-difference in hepatic very low-density lipoprotein (VLDL) assembly and secretion may contribute to NAFLD development. Estrogen-related receptor alpha (ERRα) is a key regulator of several metabolic processes. We hypothesized that ERRα plays a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 58 publications
3
44
0
Order By: Relevance
“…In this context, several studies indicate that this disparity is due to the preventive role of estrogen in hepatic steatosis (Chukijrungroat et al, 2017) among other mechanisms. Accordingly, recent studies have showed that higher hepatic estrogen-related receptor a expression in female mice contributes to the sex disparity in the assembly and secretion of hepatic triglyceride (TG)-rich very low-density lipoproteins (Yang et al, 2020). Interestingly, despite females being at lower risk of NAFLD development when comparing with males (Balakrishnan et al, 2020;Lonardo et al, 2019), rodent data support the idea that this risk can increase when liver damage is mediated by fructose intake (Choi et al, 2017;Hyer et al, 2019;Spruss et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several studies indicate that this disparity is due to the preventive role of estrogen in hepatic steatosis (Chukijrungroat et al, 2017) among other mechanisms. Accordingly, recent studies have showed that higher hepatic estrogen-related receptor a expression in female mice contributes to the sex disparity in the assembly and secretion of hepatic triglyceride (TG)-rich very low-density lipoproteins (Yang et al, 2020). Interestingly, despite females being at lower risk of NAFLD development when comparing with males (Balakrishnan et al, 2020;Lonardo et al, 2019), rodent data support the idea that this risk can increase when liver damage is mediated by fructose intake (Choi et al, 2017;Hyer et al, 2019;Spruss et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cells between passages three and ten were used and propagated in α-MEM (Gibco, USA) supplemented with 20% fetal bovine serum (FBS, Gibco, USA) and 1% penicillin–streptomycin (Gibco, USA). Mouse hepatocytes were isolated from 8 weeks old male C57 mice, and cultured in L-DMEM (Hyclone, USA) containing 10% FBS and 2% penicillin–streptomycin [ 61 ]. Cells were maintained in a humidified atmosphere containing 95% air and 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ERα-deficient mice have disrupted lipid metabolism, such as decreased fatty-acid oxidation and increased de novo lipogenesis, leading to elevated lipid accumulation in the liver compared with normal mice [ 70 , 71 , 72 ]. Similarly, downstream blocking of ERα contributed to higher visceral fat accumulation and reduced energy expenditure in female mice [ 34 , 70 , 73 ]. Meanwhile, E2 treatment promoted fatty-acid oxidation in the liver by increasing the expression of the fatty-acid transport protein, carnitine palmitoyltransferase 1 (CPT-1) [ 34 ].…”
Section: Role Of Steroid Hormones In Hepatic Steatosis and Metabolismmentioning
confidence: 99%